A catalogue of Indian Agrypninae Candèze, 1857 (Coleoptera: Elateridae) - Kotru, Akash; Chandran, Nithya; Dubey, Anil Kumar; Prosvirov, Alexander S. (Zootaxa, 2025)
For the first time, we present a catalogue on the subfamily Agrypninae in Indian context. Currently, 259 species of Agrypninae belonging to 26 genera classified into six tribes are reported from India. The tribe Agrypnini includes 154 species in eight genera, Drilini includes four species in a single genus, Hemirhipini includes 29 species in eight genera, Oophorini includes 47 species in six genera, Platycrepidiini includes one species in a single genus and Pseudomelanactini includes 24 species in two genera. The catalogue of Agrypninae from India is based on the most up-to-date family classification as well as on the recent taxonomic studies. More than half of the species of Agrypninae recorded from India are currently endemic. Twelve new combinations are proposed: for species hitherto included in Conoderus Eschscholtz, 1829 (currently a synonym of Monocrepidius Eschscholtz, 1829): Monocrepidius bicarinatus (Vats and Chauhan, 1992) comb. nov., M. chitrakutensis (Vats and Chauhan, 1992) comb. nov., M. garhwalensis (Vats and Chauhan, 1992) comb. nov., M. longipenis (Vats and Chauhan, 1992) comb. nov., M. nigripes (Vats and Chauhan, 1992) comb. nov., M. nigrolineatus (Vats and Chauhan, 1992) comb. nov., M. tapovanensis (Vats and Chauhan, 1992) comb. nov.; for species hiertho included in Paracalais Neboiss, 1967 (currently a synonym of Cryptalaus Ôhira, 1967): Cryptalaus irroratus (Parry, 1845) comb. nov.; C. lacteus (Fabricius, 1801) comb. nov., C. senecterei (Candèze, 1857) comb. nov., C. speciosus (Linnéaus, 1767) comb. nov.; and for species hitherto included in Agrypnus Eschscholtz, 1829: Compsolacon niger (Schwarz, 1905) comb. nov.